Fossil earthquake recorded by pseudotachylytes and two textural types of cataclasites from northern Langhovde in the Lützow-Holm Complex, East Antarctica - Toyoshima, Tsuyoshi; Kitano, Ippei; Ishikawa, Masahiro; Katori, Takuma; Hokada, Tomokazu (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object